Social behaviour and time budget of breeding bulls - Schwan, Lottie (SLU/Dept. of Animal Environment and Health (until 231231), 2011)
The aim of this study was to investigate the social behaviour and time budget of breeding bulls kept at VikingGenetics, Falkenberg in Sweden when the staff was off duty. It was of interest to see if there was any difference between bulls housed in group pens and bulls housed in individual pens. It was also of interest to investigate if there was any difference in the behaviour between the dairy breeds Swedish Red (SR) and Swedish Holstein (SH).